The Forms of Loanwords in Sports News in the Online Newspaper Rakyat Bengkulu - Febianto, Febianto; Yumarni , Asmara; Sari , Wenny Aulia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine the forms of loanwords in sports news in the online newspaper Rakyat Bengkulu. The research uses a qualitative approach, focusing on exploring processes, events, and developments in language use. Data were collected from Rakyat Bengkulu online during June, July, and August 2022. The study finds that loanwords in the sports news are primarily derived from English. For example, the word